A randomised controlled trial to examine the effectiveness of group cognitive behavioural therapy for the treatment of unipolar depression in Malaysia - Low, Jia Liang; Mukhtar, Firdaus; M. Sidik, Sherina; Ibrahim, Normala; Mahadevan, Raynuha; Oei, Tian P. S. (Universiti Putra Malaysia Press, 2017)
Malaysia has been experiencing a dearth in mental health resources. Group Cognitive Behavioural Therapy (GCBT) has been an established form of treatment for unipolar depression. The objectives of the current study were to examine the effectiveness of using GCBT for the treatment of depression in Malaysia. A total of 174 participants suffering from unipolar depression were recruited and randomly allocated to one of GCBT+Treatment as Usual (TAU), Relaxation training+TAU, or TAU only treatment groups. The participants were between 18-60 years of age. The participants in the GCBT+TAU group received eight Group CBT sessions of over a span of two months. The participants receiving Relaxation+TAU treatment received eight relaxation training sessions over a span of two months. The participants in the TAU only treatment group received treatment as usual from their psychiatrists. The BDI-M, ATQ-M, ATQP-M and DAS-M were administered at pre-treatment, mid-treatment (week 4) and post-treatment. Repeated Measures MANOVA showed a significant interaction effect between treatment group and time for BDI-M, ATQ-M, ATQP-M and DAS-M. Results showed that GCBT+TAU was able to significantly reduce depressive symptoms, negative cognitions and beliefs. Moderate effect sizes for the BDI-M scores, as well as significantly reliable and clinical change, were also found. The current study was limited by geographical boundaries, where only hospitals in and around the greater Klang Valley area were sampled. Results from the current study suggest that GCBT is effective in reducing the symptoms of depression in a Malaysian setting.